2020
DOI: 10.1007/s42243-020-00454-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial iron ore particle size on CO2 gasification behavior and strength of ferro-coke

Abstract: Highly reactive ferro-coke has been widely studied due to its contribution to the energy saving and emission reduction in blast furnace ironmaking. To optimize the coking process of ferro-coke and improve its metallurgical properties, it is necessary to clarify the influence of initial iron ore on the strength, micro-morphology and CO 2 gasification reaction behavior of formed ferro-coke. The effects of initial iron ore particle size (0.50-1.00, 0.25-0.50 and 0.074-0.125 mm) on the CO 2 gasification reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…The hightemperature compressive strength of iron coke with 40% iron ore content is <2000 N for carbonization temperatures of 700 and 800 °C, and <3000 N for temperatures of 900 and 1000 °C. The results above are higher than that of the previous studies in which high-temperature compressive strength of the iron coke after 60 min gasification is just 351.6 N. [24,25] It can be indicated that both the carbonization temperature and iron ore content have an effect on the high-temperature compressive strength of iron coke when roasted at 1100 °C for 60 min under a CO 2 atmosphere. The high carbonization temperature is beneficial at increasing the high-temperature compressive strength of iron coke.…”
Section: Compressive Strength Analysiscontrasting
confidence: 58%
See 1 more Smart Citation
“…The hightemperature compressive strength of iron coke with 40% iron ore content is <2000 N for carbonization temperatures of 700 and 800 °C, and <3000 N for temperatures of 900 and 1000 °C. The results above are higher than that of the previous studies in which high-temperature compressive strength of the iron coke after 60 min gasification is just 351.6 N. [24,25] It can be indicated that both the carbonization temperature and iron ore content have an effect on the high-temperature compressive strength of iron coke when roasted at 1100 °C for 60 min under a CO 2 atmosphere. The high carbonization temperature is beneficial at increasing the high-temperature compressive strength of iron coke.…”
Section: Compressive Strength Analysiscontrasting
confidence: 58%
“…They found that the cold crushing strength of iron coke decreased with increased amount of iron ore and that gasification had a strong effect on the hot compression strength due to carbon consumption. However, the highest value for the hot compression strength was just below 600 N and the best compression strength for iron coke after 60 min gasification was just 351.6 N. [24,25] Higuchi et al found that the cold strength of iron coke products decreased with an increase in the mixing ratio of iron ore. Iron coke with concentrations of iron ore up to 30% would have enough strength for use in the blast furnace as nut coke. [19] Uchida et al found that the coke strength is influenced by pore wall thickness rather than by the pores surrounding the iron particles generated by the consumption of the coke matrix during the reduction reaction of iron oxide.…”
mentioning
confidence: 99%
“…Por exemplo, a Ts diminuiu de 1080ºC para 999ºC e 957ºC com a adição de 27% e 43% de ferro, respectivamente. Outros estudos [19][20][21][22] também observaram reduções significativas na Ts com a adição de minério de ferro, variando de 55ºC a 150ºC, dependendo das condições e da proporção de minério de ferro utilizado. Além disso, outros estudos [17,18] demonstraram através de simuladores de alto-forno que a redução da Ts no CAR repercutiu em um decréscimo da temperatura da zona de reserva térmica do reator.…”
Section: Impacto Do Uso De Diferentes Fec Na Reatividade De Carunclassified
“…[ 67 ] Furthermore, Li et al [ 68 ] found that the less the gangue content in iron ore fines, the less its effect on the cold strength of iron coke would be. Wang et al [ 69 ] analyzed the effect of the initial particle size of iron ore (0.50–1.00 mm QE1, 0.25–0.50 mm QE2, and 0.074–0.125 mm QE3) on the strength of iron coke. The results showed that the initial particle size has a large effect on the strength of iron coke.…”
Section: Metallurgical Properties Of Iron Cokementioning
confidence: 99%